Horizontal fracture of anterior mandible. Issue 12 (18th December 2020) - Jain, Anuj; Rai, Anshul; Yadav, Surendra
Abstract : A 33-year-old male patient reported to us with the history of assault. The patient was cooperative and oriented, with no sign of head injury. He was assaulted with an axe over the mandible. The patient is having posteroanterior view radiographs of the mandible suggesting isolated horizontal fracture of the anterior mandible. Under general anaesthesia, this unusual fracture was treated by open reduction and internal fixation with a three-dimensional plate and miniplates. The case was managed successfully without any postoperative complications.